Kajian Unit Pengolahan Menggunakan Media Berbutir dengan Parameter Kekeruhan, TSS, Senyawa Organik dan pH - Suprihanto Notodarmojo; Andriani Astuti; Anne Juliah (Institute for Research and Community Services (LPPM) ITB, 2004)
A field trial of flocculation using gravel bed has been done using PDAM's Kota Bandung as the location. The reactor used a PVC pipe that consisted of an average diameter of 2,025 cm gravel. PDAM's raw water was used as throughout the experiment. As coagulant, PAC (Poly Alumunium Chloride) is used. The results show that the reactor can reduce the organic content down to 3,02 mg/L with the removal efficiency up to 73,17%. And it also can reduce the turbidity down to 0,5 NTU with removal efficiency up to 96%. The G.td value was 6946, which down below the average G.td used in hydraulic flocculation. Overall, the flocculation has a prospect to be used in operational scale.